2010
DOI: 10.1055/s-0029-1225325
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Anxiety in Patients Undergoing Herniated Disc Surgery: Relevant but Underresearched – A Systematic Review

Abstract: Little research has been done to investigate depression and anxiety in patients undergoing surgery for a herniated disc. Evidently disc surgery patients are at higher risk of suffering from depression and anxiety than the general population. The review outlines the importance for clinicians to be more sensitive to psychological concerns in patients undergoing disc surgery. Psychological assessment and assistance from mental health professionals should be considered during the hospital stay and rehabilitation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 32 publications
2
40
0
5
Order By: Relevance
“…This implies that compared to our study results the depression rates found by Guilfoyle et al [29] might be even higher, whereas anxiety rates might be lower right before surgery. Comparing our results to the findings of Graver et al [30], their anxiety rates of 38% [13,30] right before disc surgery seem much higher. But taking to account that Graver et al [30] used a lower cut-off value, their rates might really be analogous to the results presented in this study.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…This implies that compared to our study results the depression rates found by Guilfoyle et al [29] might be even higher, whereas anxiety rates might be lower right before surgery. Comparing our results to the findings of Graver et al [30], their anxiety rates of 38% [13,30] right before disc surgery seem much higher. But taking to account that Graver et al [30] used a lower cut-off value, their rates might really be analogous to the results presented in this study.…”
Section: Discussionsupporting
confidence: 73%
“…The few studies referring to depression and anxiety in disc surgery patients show that a large number of individuals suffer from relevant psychological symptoms [13]. These findings underline the importance of investigating the course of depression and anxiety over time.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…8,26,43,44 Some studies have shown that preoperatively increased levels of fear in patients can result in less positive postoperative outcomes. 15,44,52 High levels of fear may increase the risk of pain becoming chronic and may prolong the period of work restriction. 15,33,52 In line with these studies it was found that fear-avoidance beliefs can be predictive of surgery outcomes because preoperative anxiety and uncertainty can negatively affect postoperative recovery variables and impact negatively on mental and physical recovery after surgery.…”
Section: Introductionmentioning
confidence: 99%